Assessment of Polycyclic Aromatic Hydrocarbons in Urban Water Bodies: A Study of Rivers and Lakes in Dhaka, Bangladesh (Dhaka University Journal of Science, 2024)
Polycyclic aromatic hydrocarbons (PAHs) pose significant environmental and health risks due to their toxic properties,making their assessment in urban water bodies crucial. This study aims to evaluate the presence of three notable PAHs—anthracene, fluoranthene, and benzo[a]pyrene—in the surface water of three rivers (Buriganga, Meghna, and Turag) andtwo lakes (Hatirjheel and Gulshan) in Dhaka, Bangladesh. High-performance liquid chromatography with fluorescencedetector (HPLC-FD) was employed and validated for PAH determination, using solid phase extraction (SPE) withpreconditioned C-18 SPE cartridge for sample extraction. Calibration showed excellent linearity with correlation coefficient (R²) ≥ 0.999. The limits of detection (LODs) were 200 ng/L for anthracene and 0.63 ng/L for both fluoranthene and benzo[a]pyrene, with corresponding limits of quantification (LOQs) of 660 ng/L and 2.08 ng/L, respectively. Percent recovery was 91.38% for anthracene, 85.49% for fluoranthene, and 95.72% for benzo[a]pyrene, with relative standard deviations (RSD) of 5.27, 17.55 and 2.84%, respectively. Most water samples had PAH levels below detection limits (bdl) such as anthracene (bdl-1789.57 ng/L), fluoranthene (bdl-1309.23 ng/L), and benzo[a]pyrene (bdl-25.17 ng/L), and the detected concentrations were significantly lower than WHO and USEPA guideline values. This indicates a relatively low level of PAHs contamination in the studied water bodies.Dhaka Univ. J. Sci. 72(2): 75-83, 2024 (July)